STRATEGI KOMUNIKASI KLENTENG TITD LIONG HOK BIO DALAM MENJAGA TOLERANSI ANTARBUDAYA MELALUI KIRAB BUDAYA CAP GO MEH DI KOTA MAGELANG - Kusuma, Ivana; Rahardjo, Turnomo; Lukmantoro, Triyono (Interaksi Online, 2024)
Liong Hok Bio Temple in Magelang is a place of worship and cultural activity center that plays a crucial role in fostering tolerance and intercultural relationships. The Cap Go Meh cultural parade symbolizes tolerance, reduces antiChinese sentiment, and enhances intercultural tolerance in Magelang City. Although challenges of multiculturalism have lessened, effective communication strategies are still necessary to maintain tolerance. This study aims to analyze the communication strategies employed by TITD Liong Hok Bio Temple in the Cap Go Meh Cultural Parade in Magelang. A descriptive qualitative method with a case study approach was used, utilizing the Communication Accommodation Theory. The communication strategies used by the temple are divided into four parts: problem identification, goal setting, communication strategy formulation (communicators, target audience, messages, media, communication effects), and evaluation, which is split into summative and formative evaluations to assess success, identify obstacles, and provide suggestions for improving the quality of the Cap Go Meh Cultural Parade in the future. Data were collected through in-depth interviews. The results indicate that Liong Hok Bio Temple has effectively implemented communication strategies in the Cap Go Meh celebration. These include convergence strategies that integrate traditional culture with Chinese cultural elements to reduce potential conflicts and enhance tolerance, and divergence strategies aimed at highlighting Chinese cultural heritage and strengthening the spiritual bonds of the Liong Hok Bio Temple congregation. Although both strategies are used, the implementation predominantly features convergence strategies. The cultural parade has had a positive communication effect on increasing the knowledge and attitudes of the Magelang community 2 towards Chinese culture, as well as the potential for behavioral changes in appreciating cultural diversity